Insights into the role of tumor abnormal protein in early diagnosis of cancer: A prospective cohort study. Issue 11 (March 2020) - Li, Lu-Xi; Zhang, Bin; Gong, Rui-Zhi
Abstract : Abstract: The aim of this study was to evaluate the clinical use of tumor abnormal protein (TAP) in the diagnosis of different cancers. Totally 394 patients were divided into 4 groups, namely 100 healthy volunteers, 167 patients with cancer, 20 subjects with precancerous lesions, and 107 subjects with benign lesions. TAP was detected in 4 groups of research subjects using a TAP testing kit and examination system. We correlated TAP levels with a wide variety of clinical indicators as well as established cancer markers, including alpha fetoprotein (AFP) and carbohydrate antigen 19-9 (CA19-9). Besides, the changes of TAP level in 51 patients with liver cancer before and after surgery, and overall survival of patients with high or low TAP expression in pancreatic, gallbladder, bile duct, and liver cancers were analyzed. Statistically significant difference was observed in the TAP-positive ratio among subjects with cancer (79.6%) and precancerous lesions (45.0%) compared to the healthy volunteers (4.0%). TAP expression in different cancers was characterized by high sensitivity (79.64%), specificity (89.87%), positive and negative predictive value (85.25% and 85.71%), overall compliance rate (85.53%) but low omission and mistake diagnostic rate (20.36% and 10.13%), Youden index (0.6951). In addition, there was no significant difference among patients with different types of cancer ( χ 2 = 2.886, P = .410), and TAP expression was shown to be correlated with AFP in liver cancer ( P = .034) but not with CA19-9 in pancreatic cancer ( P = .241). Moreover, the overall survival of patients with low expression of TAP in pancreatic, gallbladder, bile duct, and liver cancers were significantly higher than of patients with high expression of TAP. Compared with the preoperative patients with cancer, TAP levels decreased dramatically among postoperative subjects ( P < .001). In summary, TAP might hold promise in serving as universal indicator for the diagnosis of different cancers.